Dunia Kehidupan Pesantren Salaf dengan Dunia Sistem Pemerintah dalam Upaya Pencegahan dan Penanganan Covid-19 - Muhammad Imam Mahmudi (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2021)
Life in a salafiyah Islamic boarding school is unique from other educational institutions. The uniqueness of these Salafiyah Islamic boarding schools, among others, in managing and regulating their institutions, the Islamic boarding schools do not participate and even reject government regulations or policies. In the Covid-19 case, the Salafiyah Islamic boarding school Miftahul Huda obeyed and implemented government regulations. Therefore, the researcher wants to examine the suitability that gives rise to this consensus with Habermas' critical theory. Here we will study the rationalization of the life-world of Salafiyah Islamic boarding schools and the world of government systems that have led to a consensus that is carried out by both harmoniously.